GEL TIME STUDIES IN ACTIVATION OF POLYESTER RESIN - BALASUBRAMANYAN, R (Fishery Technology, 2025)
GeUing times of po yester resins with varying quantities of catalyst and accelerator were studied and the resuHs !reported in this communication.